A Lost Legendary Humane Common Properties Called Peace and Coexistence of Homo Muslimus in Jerusalem - Öztürk, Ali; Açıköz, Mustafa (Akademik Perspektif Derneği, 2018)
In this joint article, we shall deal with Jerusalem and its three historic faces of ‘homo Muslimus’ (i.e. Judaistic, Christian and Islamic traditions as three religious faces of Abraham at the sample of both his biological and religious family tree traced back to Adam) have been recorded in ‘Jerusalem’ City as to peaceful co-existence. Our inquiry stand points will be based on the philosophico-sociological ground as well as the history of Divine religions. Jerusalem is one of the oldest habitats of Adam’s children. The members of Adamhood had been mentally and spiritually evolved by divine intervention from the state of homo sapiens to the state of, what we call, homo skeptikus so as to be a good and a model homo Muslimus on the earth in the very long journey of divine evolution. Thus one of the largest groups of homo Muslimus and civilizations historically known as members of Abrahamic religions and their followers have been living together in Jerusalem city as a nucleus sample. All homo skeptikus reason porters have been divinely formatted by God in their very nature as people of peace and co-existence to talk and act during their stay on the earth. However both historical records of homo skeptikus reason porter in general and of homo Muslimus in particular led us to think that having and practising culture of peace and coexistence was/is not easy on the earth. As a world famous old city, such historical case have been happened and observed at the sample of social, religious and cultural habitat of Jerusalem. Therefore today we desperately need ‘peace’ and ‘coexistence’ all over the world as well as Jerusalem City for the wellness and welfare of humanity at global and even at universal levels. However, the question is to be answered: How is it so? In this context in the realization process of the joint paper our aim will be to draw participants’ attention to two main historic points of homo sapiens and thus discuss the outcome. These are: i) histories of homo Muslimus and Jerusalem as a city of various cultures; and ii) the historic relation between three faces of ‘homo Muslimus’ and ‘Jerusalem’ as to (regional and global) ‘peace’ and ‘coexistence’.

In this joint article, we shall deal with Jerusalem and its three historic faces of ‘homo Muslimus’ (i.e. Judaistic, Christian and Islamic traditions as three religious faces of Abraham at the sample of both his biological and religious family tree traced back to Adam) have been recorded in ‘Jerusalem’ City as to peaceful co-existence. Our inquiry stand points will be based on the philosophico-sociological ground as well as the history of Divine religions. Jerusalem is one of the oldest habitats of Adam’s children. The members of Adamhood had been mentally and spiritually evolved by divine intervention from the state of homo sapiens to the state of, what we call, homo skeptikus so as to be a good and a model homo Muslimus on the earth in the very long journey of divine evolution. Thus one of the largest groups of homo Muslimus and civilizations historically known as members of Abrahamic religions and their followers have been living together in Jerusalem city as a nucleus sample. All homo skeptikus reason porters have been divinely formatted by God in their very nature as people of peace and co-existence to talk and act during their stay on the earth. However both historical records of homo skeptikus reason porter in general and of homo Muslimus in particular led us to think that having and practising culture of peace and coexistence was/is not easy on the earth. As a world famous old city, such historical case have been happened and observed at the sample of social, religious and cultural habitat of Jerusalem. Therefore today we desperately need ‘peace’ and ‘coexistence’ all over the world as well as Jerusalem City for the wellness and welfare of humanity at global and even at universal levels. However, the question is to be answered: How is it so? In this context in the realization process of the joint paper our aim will be to draw participants’ attention to two main historic points of homo sapiens and thus discuss the outcome. These are: i) histories of homo Muslimus and Jerusalem as a city of various cultures; and ii) the historic relation between three faces of ‘homo Muslimus’ and ‘Jerusalem’ as to (regional and global) ‘peace’ and ‘coexistence’.
A Lost Legendary Humane Common Properties Called Peace and Coexistence of Homo Muslimus in Jerusalem
Keywords: Religious Studies; Din Araştırmaları